The role of oxidative post-translational modifications in type 1 diabetes pathogenesis - Alhamar, Ghadeer; Vinci, Chiara; Franzese, Valentina; Tramontana, Flavia; Le Goux, Nelig; Ludvigsson, Johnny; Nissim, Ahuva; Strollo, Rocky (Frontiers in Immunology, 2025)
The pathogenesis of type 1 diabetes (T1D) involves a complex interplay of genetic predisposition, immune processes, and environmental factors, leading to the selective destruction of pancreatic beta-cells by the immune system. Emerging evidence suggests that intrinsic beta-cell factors, including oxidative stress and post-translational modifications (PTM) of beta-cell antigens, may also contribute to their immunogenicity, shedding new light on the multifaceted pathogenesis of T1D. Over the past 30 years, neoepitopes generated by PTMs have been hypothesized to play a role in T1D pathogenesis, but their involvement has only been systematically investigated in recent years. In this review, we explored the interplay between oxidative PTMs, neoepitopes, and T1D, highlighting oxidative stress as a pivotal factor in immune system dysfunction, beta-cell vulnerability, and disease onset.